Consumo de cannabis e indicadores sociais da diferença - Melo, Ricardo Bandeira de (2020)
Through scientific literature about crime and deviance, we can find a myriad of empirical studies that shows the existence of a tendency from the justice system and from police of acting more incisively on certain social groups. As a rule, large-scale structural differences, such as racial or class differences, are taken This research aims, similarly, to comprehend the differential imposition of rules for the same practice performed by individuals with different profiles; but on a much smaller scale: developed in São Lourenço da Mata – a small city that transits between the rural world and the urban periphery, located in the Metropolitan Region of Recife, Pernambuco – between March and December 2019, with twenty semi-structured interviews, a group of people which presented low variation in terms of income, housing, race, age and other social markers of difference were analyzed. The only variable that made it possible to divide the statements into two blocks – using the patterns found a posteriori – was the level of education. Respondents with a complete or ongoing higher education showed great effort to keep marijuana use hidden from the eyes of family, neighborhood, and people in general, in addition to showing concern with developing strategies to avoid the police. On the other hand, respondents with a high school education or below did not have the same concern to hide their practice or avoid the police. The two blocks of speech present great differences in terms of use routines, meanings attributed to marijuana, and other drugs and motivations for consumption. However, the data that causes greater astonishment is how those with lower levels of education feel stigmatized and the great occurrence of approaches and police violence.